Information culture turned to the higher education institute: values and beliefs as central elements - Sambo, Acia Domingos Cumbane [UNESP]; Woida, Luana Maia (Universidade Estadual de Campinas, 2024)
Introduction Informational culture involves fundamental criteria, values and beliefs, which reflect on informational behavior consisting of the way information is interpreted and handled by individuals and groups, information favors productivity and the ability to perform routine work. The objective of the research was to analyze the informational culture aimed at the Institution of Higher Education (HEI), favoring that the background is constituted in Mozambique, and that it is consolidated from the values of the organization's philosophy on the part of its members, whose main members are professors, students and employees. Methodology, exploratory bibliographical research and a qualitative approach were used, seeking various sources, from scientific articles and theses that discuss the theme, prioritizing consultation with the BRAPCI database. Results, it is necessary to understand the informational culture, as it interferes in the construction and use of HEI norms and policies, stimulating acceptable and expected forms of behavior and information sharing, finally, Conclusion the values oriented to IC is based on new knowledge, continuous learning among professors, students and employees of HEIs in as in the hierarchical distribution, in the access, search and production of scientific and administrative knowledge.
Cultura informacional voltada para instituições de ensino superior: valores e crenças como elementos centrais
Keywords: Higher education; Information culture; Organizational culture; Values